1995
DOI: 10.1016/0032-3861(95)96857-5
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and orientation of end-grafted (co)polyglutamates and (co)polyaspartates

Abstract: The conformation and orientation of end-grafted (co)polyglutamates and (co)polyaspartates were investigated using several infra-red spectroscopy techniques. The grafted polymers took on the same conformations as the corresponding free polymers; however, the change in conformation at higher temperatures did not take place. The orientation of the polymers grafted onto flat surfaces turned out to be bent towards the surface, but became more perpendicular after interdiffusion of truns-ethyl-0-apo-8'carotenoate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Synthetic poly(γ-alkyl-α- l -glutamates) are polypeptides known to exist in a well-defined α-helical structure and retain this conformation even in solution. The α-helical structure of many polyglutamates is stabilized by intramolecular hydrogen bonding which gives the polypeptide a rodlike structure. The grafting of such polypeptides to different surfaces has been explored in association with various applications, including the separation of optical isomers, , and membrane permeability control through the helix-to-coil transition. , Poly(γ-stearyl-α- l -glutamate) (PSLG) is less often studied than poly(γ-benzyl-α- l -glutamate) (PBLG) or poly(ε-carbobenzoxy- l -lysine) (PCBL); unlike these mainstays, it has the desirable feature of being soluble in nonpolar organic solvents. PSLG features an α-helical backbone surrounded by long, flexible side chains and is often called a hairy rodlike polymer. , The stearyl chains impart good solubility to this polypeptide, which shows both lyotropic and thermotropic properties. PSLG-grafted membranes have been shown to increase the activity retention and thermal stability of lipases immobilized on them, which is due to the enhanced hydrophobic interaction between the lipase and the long stearyl chains. , Sackmann suggested that hairy rod polymers such as PSLG can be deposited on substrates, which can be further used to support biomimetic membranes by a self-assembly process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic poly(γ-alkyl-α- l -glutamates) are polypeptides known to exist in a well-defined α-helical structure and retain this conformation even in solution. The α-helical structure of many polyglutamates is stabilized by intramolecular hydrogen bonding which gives the polypeptide a rodlike structure. The grafting of such polypeptides to different surfaces has been explored in association with various applications, including the separation of optical isomers, , and membrane permeability control through the helix-to-coil transition. , Poly(γ-stearyl-α- l -glutamate) (PSLG) is less often studied than poly(γ-benzyl-α- l -glutamate) (PBLG) or poly(ε-carbobenzoxy- l -lysine) (PCBL); unlike these mainstays, it has the desirable feature of being soluble in nonpolar organic solvents. PSLG features an α-helical backbone surrounded by long, flexible side chains and is often called a hairy rodlike polymer. , The stearyl chains impart good solubility to this polypeptide, which shows both lyotropic and thermotropic properties. PSLG-grafted membranes have been shown to increase the activity retention and thermal stability of lipases immobilized on them, which is due to the enhanced hydrophobic interaction between the lipase and the long stearyl chains. , Sackmann suggested that hairy rod polymers such as PSLG can be deposited on substrates, which can be further used to support biomimetic membranes by a self-assembly process .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The R-helical structure of many polyglutamates is stabilized by intramolecular hydrogen bonding which gives the polypeptide a rodlike structure. The grafting of such polypeptides to different surfaces has been explored [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] in association with various applications, including the separation of optical isomers, 19,27 and membrane permeability control through the helix-to-coil transition. 26,27 Poly(γ-stearyl-R-L-glutamate) (PSLG) is less often studied than poly(γbenzyl-R-L-glutamate) (PBLG) or poly(ε-carbobenzoxy-L-lysine) (PCBL); unlike these mainstays, it has the desirable feature of being soluble in nonpolar organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages some authors tried the so-called ”grafting-from” method. , This method uses relatively small monomers, which can easily reach the initiator sites on the substrate. So, these polymers actually grow from the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In the “grafting-from” method, immobilized initiators on substrates are brought in contact with dissolved monomers to obtain covalently bonded polymer chains on the substrate. Primary amines can be used as initiators for the ring-opening polymerization of N -carboxyanhydrides of various amino acid esters.…”
Section: Introductionmentioning
confidence: 99%